Decarbonizing Nepal’s Cement Industry with Hydropower-Based Hydrogen - Khanal, Rishav (Everest Advances in Science and Technology, 2025)
The cement industry is a significant global source of CO2 emissions, with Nepal’s clinker production contributing approximately 2.34 million metric tons annually through coal combustion. This study investigates the technical and economic feasibility of decarbonizing Nepal’s cement sector by transitioning to green hydrogen fuel, leveraging the country’s abundant hydropower resources. Through detailed energy balance calculations and techno-economic modeling, we demonstrate that complete coal replacement would require 227,743 metric tons of green hydrogen annually, necessitating 2,002 MW of dedicated hydropower capacity. Our projections indicate hydrogen production costs could decline to $2.15/kg by 2035, driven by electrolyzer efficiency improvements and Nepal’s competitive industrial electricity tariffs. The analysis reveals this transition could eliminate up to 2.57 million metric tons of CO2 emissions yearly, representing a 98% reduction in fuel combustion emissions. However, implementation challenges include seasonal hydropower variability, requiring 2,000 MW of reservoir projects, and substantial infrastructure investments estimated at $800 million. The study proposes a phased adoption pathway, with 30% hydrogen penetration by 2030 achieving 770,000 metric tons of annual emission reductions. We identify critical policy interventions including a $139/ton carbon price and targeted subsidies to bridge the current cost gap. A $139/ton carbon price and targeted subsidies are identified as key policy interventions to bridge the current cost gap.